1996
DOI: 10.1007/bf00295891
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate transport and calcium oxalate renal stone disease

Abstract: Hyperoxaluria is considered to play a crucial role in calcium oxalate (CaOx) renal stone disease. The amount of oxalate excreted into the urine depends on intestinal absorption, endogenous production, renal clearance and renal tubular transport. Since a primary disorder has not been found so far in most CaOx stone formers and since oxalate is freely filtered at the glomerulus, most studies are presently focussed on alterations in epithelial oxalate transport pathways. Oxalate can be transported across an epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Oxalate undergoes bidirectional transport in the proximal tubule with overall net secretion (78). Perfusion studies demonstrate net absorption of oxalate by the S1 and S2 segments of the rat proximal tubule and net secretion by the S3 segment (34,51).…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate undergoes bidirectional transport in the proximal tubule with overall net secretion (78). Perfusion studies demonstrate net absorption of oxalate by the S1 and S2 segments of the rat proximal tubule and net secretion by the S3 segment (34,51).…”
Section: Discussionmentioning
confidence: 99%
“…A temporal and significant increase of serum Cr and UN levels was observed in Groups B and C compared to values obtained for Groups A and D (P < 0.05). Ox levels in serum and urine were significantly higher in Groups A and B than in the other two groups from day 7 urinary stones [8,9], although this notion was challenged by others [10] proposing hypercalciuria to be the prime metabolic ailment involved in stone formation.…”
Section: Introductionmentioning
confidence: 92%
“…As proposed previously, hyperoxaluria is considered a major risk factor for urinary stone, and experimental induction of hyperoxaluria can lead to crystalluria and CaOx crystal deposition in the kidney [6,7]. In addition, recurrent idiopathic stone formers always show mild hyperoxaluria; meanwhile, amount and size of CaOx crystals, alongside disease severity, are highly related to urinary excretion of oxalate (Ox) [8]. Many studies suggested a more pronounced role for hyperoxaluria than that of hypercalciuria in the formation of Abstract Hyperoxaluria and cell injury are key factors in urolithiasis.…”
Section: Introductionmentioning
confidence: 98%
“…20 The effective radius of oxalate has been estimated to be around 3 to 4 Å on the basis of its structure and negative charge size. 21 In addition, oxalate forms soluble complexes with Na ϩ , Ca ϩϩ , and Mg ϩϩ that can increase its calculated size. 22 Mannitol has an estimated size of 4.2 Å 18 and has been demonstrated to traverse the size-independent "leak" pathway.…”
Section: Effect Of Inducing Claudin-10a Expression On Tight Junction mentioning
confidence: 99%